2003
DOI: 10.1002/jclp.10151
|View full text |Cite
|
Sign up to set email alerts
|

Role of family in the management of Type‐I diabetes: An Indian experience

Abstract: The role of the family in the management of Type-I diabetes is gaining recognition. In countries where the adolescent is dependent on the family for medical needs, the family's role is all the more important. At times, when the family is uncooperative, the care of the adolescent is hampered, making psychosocial intervention even more difficult. The following case study illustrates the difficulty encountered while working with a young diabetic belonging to an Indian family. The issues related to parental role a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[17] The importance of family education and psychosocial intervention is described in an adolescent with type 1 diabetes. [8] Other research reports identified that 40% patients do not disclose the details about their diabetes and an episode of hypoglycemia is a motivating factor for the same. [7,11] Sleep disorders were associated with the presence of microvascular complications and is responsible for hyperglycemia leading into a vicious cycle.…”
Section: Discussionmentioning
confidence: 99%
“…[17] The importance of family education and psychosocial intervention is described in an adolescent with type 1 diabetes. [8] Other research reports identified that 40% patients do not disclose the details about their diabetes and an episode of hypoglycemia is a motivating factor for the same. [7,11] Sleep disorders were associated with the presence of microvascular complications and is responsible for hyperglycemia leading into a vicious cycle.…”
Section: Discussionmentioning
confidence: 99%